A numerical algorithm for gas foil bearing simulation with considering three-dimensional structure - He, Weipei; Feng, Ming; Ren, Tianming (Mechanical systems and signal processing, 2024)
This paper presents a coupled algorithm for gas foil bearing simulation with considering three-dimensional structure. In the discretization process of the top foil, the plate and shell elements are compared to evaluate their advantages in terms of computational time and deviation. Based on the displacement constraints, the bump foil is simplified as a series of separated bumps and their interaction forces are calculated by the penalty function method. To solve the nonlinearity of the foil deflection caused by the frictional contact, the incremental iteration method is introduced in the simulation. The calculation accuracy of the proposed algorithm is verified by the experimental results and its efficiency is superior to the existing methods.